2009
DOI: 10.4067/s0717-95022009000200021
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Alterations of the Surfaces of Enamel and Dentin of Deciduous Teeth Irradiated with Nd:YAG, C0(2)and Diode Lasers

Abstract: SUMMARY:In this work, we studied the effects of CO 2 , Nd:YAG and diode lasers on the enamel and dentin of deciduous human teeth. After the irradiations, the samples were duly prepared and set up on metallic bases, covered with gold and examined in the scanning electron microscope. The results showed that the irradiation with the CO 2 mode locked laser with 1.0 W power caused melting and irregularities with small cavities on the surface of the enamel. The irradiated area on the dentin surface appeared circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
10
1
Order By: Relevance
“…In this study, we found that 2 times laser irradiation had no significant effect on the suppression of the enamel microhardness reduction, which is in contrast to the results of 4 times irradiation in our study and 2 previous studies by Souza et al 32 and da Silva Barbosa et al 19 Souza et al 32 studied the effects of the CO2, Nd:YAG and diode lasers with 1.0 W power and 84.9 J/cm 3 energy on the enamel of deciduous human teeth via scanning electron microscope. They showed the formation of a melted and evenly resolidified enamel surface, suggesting an increase in the resistance of the dental enamel against acids.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that 2 times laser irradiation had no significant effect on the suppression of the enamel microhardness reduction, which is in contrast to the results of 4 times irradiation in our study and 2 previous studies by Souza et al 32 and da Silva Barbosa et al 19 Souza et al 32 studied the effects of the CO2, Nd:YAG and diode lasers with 1.0 W power and 84.9 J/cm 3 energy on the enamel of deciduous human teeth via scanning electron microscope. They showed the formation of a melted and evenly resolidified enamel surface, suggesting an increase in the resistance of the dental enamel against acids.…”
Section: Discussioncontrasting
confidence: 99%
“…30,31 There are hardly any studies on the effects of the diode laser on the dental structure, especially using enamel microhardness. Indeed, to the best of our knowledge, only four previous studies investigated the effect of the diode laser on deciduous teeth 17,19,20,32 and only one of them studied the enamel microhardness changes either with or without fluoride application. 19 Thus, the effect of the diode laser on the ultrastructure of the enamel and its ability to reduce enamel microhardness loss after acid challenge is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Scanning electron microscopy analysis revealed significant morphological alterations of the Nd:YAG diode (808 and 980 nm) and Er,Cr:YSGG laser-irradiated enamel surface, like melting and recrystallization, cracks and porosities (12,15,16). However, it is unclear whether those effects alter significantly the roughness of the dental enamel.…”
Section: Introductionmentioning
confidence: 99%
“…5,22,23 Laser desensitization is also a novel and efficient alternative for the immediate treatment of dentinal hypersensitivity. [24][25][26][27][28] Lasers are being investigated for the treatment of hypersensitivity as a monotherapy or in combination with desensitizing agents incorporated in toothpaste in regular use by patients. 17,[29][30][31] Presently there is no standard protocol of treatment for the same.…”
Section: Introductionmentioning
confidence: 99%